The supervisory role of competition boards over economic concentration operations: (Comparative analytical study) - Latif, Adnan Baqi; Mahmmod, Peshawa Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
Economic concentrations are one of the most important means that projects seek to in order to acquire or enhance economic power to stand up to competitors, the concept of these concentrations includes all operations that would lead to an increase in the size of economic units and those that aim to achieve economic integration between joint projects in the process of concentration. Also, transferring the authority of control and controlling over a group of economic projects to one of them that has the ability to impose economic policy on other projects. In addition, some of these actions may result in giving some of the economic concentrations that are established by the organizations a dominant position or strengthening them in a way that could damage value of competitions in the market. Therefore, most of the legislations related to the protection of competitions have forced the application of control over the operations of economic concentration in order to balance between the interests of the projects stationed and the interests of competitors in one particular market. Also, the interest of the national economy that both previous interests are included in; however, the law of competition and prevention of monopoly in Iraq No. (14) for the year of 2010, completely neglected the enforcement role of the Competition Affairs Council that can exercise over economic concentrations, and there is no legal text or code involving the execution of the council’s supervisory role. For this reason, this study is titled "The Supervisory Role of Competition Councils on Economic Concentration Operations" with the aim of establishing solid legal rules for monitoring economic concentrations in the market and providing effective solutions to the Iraqi legislature to address this legislative deficiency.